An economic evaluation of a telephone outcall intervention for informal carers of cancer patients in Australia: An assessment of costs and quality‐adjusted‐life‐years. Issue 3 (15th January 2019) - Richards‐Jones, Scott; Mihalopoulos, Cathrine; Heckel, Leila; Gunn, Kate M.; Tan, Marcus; Livingston, Patricia M.
Abstract: Objective: Carers of people with cancer provide uncompensated care that is often physically, emotionally, and financially demanding, which results in neglect of their own health. This study's objective was to conduct an economic evaluation following a randomised control trial (RCT) involving a proactive telephone outcall intervention aimed at improving health outcomes among carers of cancer patients. Methods: The trial was a single‐blind, multicentre, RCT conducted across four Australian health services, comprising three outcalls from trained Cancer Council 131120 (Cancer Council telephone and information support services) nurses compared with three phone call reminders of the availability of 131120 services (control group). Outcalls consisted of telephone contacts to the caregivers initiated by the Cancer Council nurses. The primary trial outcome was reduced carer burden. Health care resource use was measured using a resource use questionnaire (RUQ), and costs were presented in 2013 (AUS). Quality‐adjusted‐life‐years (QALYs) were also used as health outcomes. An incremental cost‐effectiveness ratio (ICER) was calculated, with bootstrapping used to quantify sampling variability. A 50 000 per QALY‐gained willingness‐to‐pay threshold was used. Sensitivity analyses were conducted. Results: Results showed that the total mean QALYs‐gained were higher (0.02 QALYs, P = 0.01) in the control group, and total mean costs were lower in the control group (477, P < 0.001) over the trial duration. The intervention group was dominated by the control group. Results were robust to sensitivity analyses. Conclusions: Results suggest policy makers should not adopt this intervention into routine health care in its current form. Further research into the efficacy and cost‐effectiveness of telephone‐based interventions for carers is required.